İSLAM MANTIK GELENEĞİNDE FENARİ’NİN YERİ (Fenari Şerhi ve İçeriği Üzerine) - Ahmet Kayacık (İslami İlimler Dergisi)
Al-Fanari who lived in florishing time of Ottaman State was a scholar, professor and offical for goverment. Including logic he wrote many works in different fields. This article is about Farari’s commentary on Abhari’s Isagoge and about its content. By the way it was talked about the role or place of Fanari in this field, logic. This work that written on many glosses or super glosses, until now performed a good work in madrasas; and if we take this work for present readers or students we can say it is still preserving its value and importance.